The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33448/rsd-v9i10.8407
|View full text |Cite
|
Sign up to set email alerts
|

Is ozone effective in reducing pain, edema, and trismus after third molar surgery? A systematic review

Abstract: This study aimed to evaluate the efficacy of ozone as a supporting therapy in reducing pain, edema, and trismus after lower third molar extraction. The protocol was registered in PROSPERO. Six electronic databases (PubMed, Scopus, LILACS, SciELO, Embase, and Web of Science) were used. Only randomized clinical trials were included, without restriction of year, language, and publication status. The JBI tool was used to assess the risk of bias. The GRADE approach assessed the certainty of evidence. The search yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…In the present study in the control group the pain increases gradually starting from the 2nd day and reaches a maximum on the 3rd day and then decreases abruptly in the 5th and 6th days. In comparison be-tween our study with the other study, the results of the present study are in disagreement with Ricardo Pedro da Silva 22 who found in his study that the use of ozone gel as a supportive therapy may be effective in reducing pain and agreement with Alkholy S.S.et al 5 they found in their study that the patients of ozone gel group had the least pain than the other groups. In my study, the evaluation of pain daily was based on the criteria given by samad et al, 12 the use of ozone gel cause increase in serotonin and endogenous opioids has been shown after Oxygen-Ozone administration and these antioxidant molecules could induce pain relief by stimulating antinociceptive pathways 1 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study in the control group the pain increases gradually starting from the 2nd day and reaches a maximum on the 3rd day and then decreases abruptly in the 5th and 6th days. In comparison be-tween our study with the other study, the results of the present study are in disagreement with Ricardo Pedro da Silva 22 who found in his study that the use of ozone gel as a supportive therapy may be effective in reducing pain and agreement with Alkholy S.S.et al 5 they found in their study that the patients of ozone gel group had the least pain than the other groups. In my study, the evaluation of pain daily was based on the criteria given by samad et al, 12 the use of ozone gel cause increase in serotonin and endogenous opioids has been shown after Oxygen-Ozone administration and these antioxidant molecules could induce pain relief by stimulating antinociceptive pathways 1 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the antibiotic group (control group) the swelling increases gradually starting from the 2nd day and reaches a maximum on the 3rd day then decreases gradually from the 6th and 7th days. In comparison between our study with the other study, the results of our study are in disagreement with Kazancioglu HO et al 26 and Recardo Pedro da Silva 22 they found in their study the ozone gel had minimal effect on swelling and in agreement with Sivalingman et al 16 and Shokry et al 27 they found that swelling had reduced and resolved more rapidly in the ozone gel group than the antibiotic group. Trismus (Greek -trismos) is defined as a prolonged tetanic spasm of masticatory muscles of the jaw.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in agreement with those of Kazancioglu et al, 16 Sivalingam et al, 20 Silva et al, 45 and Bahl et al, 53 who showed that ozone can lessen postoperative pain following surgical removal of the mandibular third molar. However, ozone had no beneficial effect on pain, per the findings of research carried out by Gloria et al 46 The results of the current study indicated that ozone had no statistically significant impact on trismus.…”
Section: Discussionsupporting
confidence: 92%